Beyond the western sea. Book II, Lord Kirkle's money - Avi, 1937- (New York : Avon Camelot, 1998)
Driven from their impoverished Irish village, fifteen-year-old Maura and her younger brother meet their landlord's runaway son in Liverpool while all three wait for a ship to America; their fates continue to intertwine on board ship and in the New World.
Elem. School Library Collection.
School Library Journal.
Wilson's Junior High School.
5.5.
5.9
5-8
Keywords: Adventure and adventurers -- Fiction; Emigration and immigration -- Fiction; Historical fiction; Runaways -- Fiction; Adventure fiction; Historical fiction; Immigration and emigration -- Fiction; Runaway teenagers -- Fiction; England -- Fiction; Ireland -- Fiction; England -- Fiction; Ireland -- Fiction